Pengelolaan Hubungan Sekolah dan Masyarakat - Nurul Fauzani Rosyida; Hanin Dewi Septiyaningtiyas; Irawan Sukma; Riznaini Ika Utami; Dela Fauziyatul Muzakkiyah; Bahtiyar Heru Susanto (STIKes Ibnu Sina Ajibarang, 2024)
Management of school and community relations is a process of mutual collaboration between the school and the community to achieve or make programs a success. The implementation of these programs is carried out through collaboration using various media such as print media, electronic media, communities and most importantly involving the surrounding community. If a system does not have management, it will disintegrate or become a system without rules. Especially in the relationship between school and community because there are several things that must be managed (management) which are elements of education itself, for example, there are educational staff, students, materials, tools and methods that must be launched.The main objective in exploring the theme of managing school and community relations is to analyze and describe the topics above, and explore case studies and solutions that will be used. This technique uses the term